2003
DOI: 10.1128/jcm.41.2.838-840.2003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Urinary Antigen Detection for Diagnosis of Community-Acquired, Travel-Associated, and Nosocomial Legionnaires' Disease

Abstract: The clinical utility of Legionella urinary antigen assays for the diagnosis of Legionnaires' disease was assessed by using samples from 317 culture-proven cases. The sensitivities of the Binax enzyme immunoassay (EIA) and Biotest EIA were found to be 93.7 and 94.4% for travel-associated infection and 86.5 and 76.0% for community-acquired infection but only 44.2 and 45.7% for nosocomially acquired infection, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
1
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(102 citation statements)
references
References 18 publications
(9 reference statements)
2
82
1
15
Order By: Relevance
“…1). Helbig et al (2003) found an overall sensitivity of 80.6 % for the Binax EIA, which is in accordance with our result. Yzerman et al (2002) found a sensitivity of 69 % for Binax EIA and 72 % for BinaxNOW for unconcentrated urine samples, but an increase in sensitivity of approximately 10 % for concentrated samples.…”
Section: Discussionsupporting
confidence: 82%
“…1). Helbig et al (2003) found an overall sensitivity of 80.6 % for the Binax EIA, which is in accordance with our result. Yzerman et al (2002) found a sensitivity of 69 % for Binax EIA and 72 % for BinaxNOW for unconcentrated urine samples, but an increase in sensitivity of approximately 10 % for concentrated samples.…”
Section: Discussionsupporting
confidence: 82%
“…A vast majority of community‐acquired LP cases are caused by this species and serogroup 4, 17, 18. Although it is very useful to define a diagnosis of LP, it is of limited use to detect non‐serogroup 1  L. pneumophila and other species.…”
Section: Discussionmentioning
confidence: 99%
“…The PUatg is widely used and increases the number of etiologic diagnosis 14,15,16 . In our setting the sensitivity was 36% (CI 95% 10-62), conferring the test low precision in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In what concerns the use of PUatg in Healthcare Associated Pneumonias (HCAP), the evidence in literature is scarce, its usefulness in this context is controversial and the main societies don't recommend it [15][16][17] . However, in clinical practice, the test is frequently requested, so we decided to include these patients to clarify the role of the PUatg in this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation